2000
DOI: 10.1002/(sici)1521-3765(20000303)6:5<767::aid-chem767>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

New Polyfunctional Magnesium Reagents for Organic Synthesis

Abstract: The iodine-magnesium exchange reaction allows the preparation of polyfunctional aryl, heteroaryl, or alkenyl magnesium reagents at low temperature. These reagents display the typical reactivity of Grignard compounds and undergo various copper-catalyzed reactions such as allylation or 1,4-addition. Using this halogen-metal exchange reaction, it was possible to generate polyfunctional magnesium reagents on the solid phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 12 publications
1
39
0
3
Order By: Relevance
“…[36] The use of highly active magnesium, such as ªRieke-magnesiumº, [37] is not possible since the presence of electron-poor functional groups such as a carboxy or cyano group inhibits the formation of the Grignard reagent. [39] The mild conditions required for the bromine ± magnesium exchange were first discovered by Villie  ras who demonstrated that highly reactive magnesium carbenoids such as 35 can be prepared at À 78 8C. [39] The mild conditions required for the bromine ± magnesium exchange were first discovered by Villie  ras who demonstrated that highly reactive magnesium carbenoids such as 35 can be prepared at À 78 8C.…”
Section: Polyfunctional Organomagnesium Reagentsmentioning
confidence: 99%
“…[36] The use of highly active magnesium, such as ªRieke-magnesiumº, [37] is not possible since the presence of electron-poor functional groups such as a carboxy or cyano group inhibits the formation of the Grignard reagent. [39] The mild conditions required for the bromine ± magnesium exchange were first discovered by Villie  ras who demonstrated that highly reactive magnesium carbenoids such as 35 can be prepared at À 78 8C. [39] The mild conditions required for the bromine ± magnesium exchange were first discovered by Villie  ras who demonstrated that highly reactive magnesium carbenoids such as 35 can be prepared at À 78 8C.…”
Section: Polyfunctional Organomagnesium Reagentsmentioning
confidence: 99%
“…This was indeed the case as demonstrated by the isomerization of (Z)-1-triphenylgermyl-1-dodecene into the (E)-isomer. Heating a benzene solution of (Z)-1-triphenylgermyl-1-dodecene at 60 C in the presence of catalytic amounts of Ph 3 GeH and Et 3 B gave (E)-isomer exclusively. The isomerization is explained by addition-elimination sequences of the triphenylgermyl radical (Scheme 14).…”
Section: Et 3 B-induced Radical Addition Of R 3 Snh and R 3 Geh To Acmentioning
confidence: 99%
“…Knochel et al have reported the halogen-magnesium exchange for the preparation of polyfunctional organomagnesium reagents. 60,61 Aryl, heteroaryl, and alkenyl halides bearing electron-withdrawing groups or metal-directing groups can be converted into the corresponding magnesium reagents by treating with i-PrMgBr or i-Pr 2 Mg in THF at low temperatures. However, substrates are often limited to rather electron-poor aryl or alkenyl halides, particularly in the case of bromides.…”
Section: 59mentioning
confidence: 99%
“…Unfortunately, the presence of such important electron-withdrawing functional groups as esters or cyano functions inhibits the formation of Grignard reagents [18]. Complementarily, halogen-magnesium exchange [19] has proven to be an excellent method for preparation of functionalized organomagnesium compounds. Thus, treatment of 4-iodobenzonitrile 13 with iPrMgBr or iPr 2 Mg in THF at À25 C furnishes the corresponding organomagnesium reagent, which is transmetalated to produce the desired functionalized organocopper 14.…”
Section: Transmetalation Reactions Producing Organocopper Reagentsmentioning
confidence: 99%
“…After cleavage from the resin, a range of functionalized products may be obtained. Use of the resin-bound bromothiophene 41 as starting material furnishes the copper reagent 42, which produces the carboxylic acid 43 after allylation and cleavage from the resin (Scheme 2.10) [19,24]. …”
Section: Transmetalation Reactions Producing Organocopper Reagentsmentioning
confidence: 99%